CircSERPINE2 protects against osteoarthritis by targeting miR-1271 and ETS-related gene. Issue 6 (28th March 2019) - Shen, Shuying; Wu, Yizheng; Chen, Junxin; Xie, Ziang; Huang, Kangmao; Wang, Gangliang; Yang, Yute; Ni, Weiyu; Chen, Zhijun; Shi, Peihua; Ma, Yan; Fan, Shunwu
Abstract : Objectives: Circular RNAs (circRNA) expression aberration has been identified in various human diseases. In this study, we investigated whether circRNAs could act as competing endogenous RNAs to regulate the pathological process of osteoarthritis (OA). Methods: CircRNA deep sequencing was performed to the expression of circRNAs between OA and control cartilage tissues. The regulatory and functional role of CircSERPINE2 upregulation was examined in OA and was validated in vitro and in vivo, downstream target of CircSERPINE2 was explored. RNA pull down, a luciferase reporter assay, biotin-coupled microRNA capture and fluorescence in situ hybridisation were used to evaluate the interaction between CircSERPINE2 and miR-1271-5 p, as well as the target mRNA, E26 transformation-specific-related gene (ERG). The role and mechanism of CircSERPINE2 in OA was also explored in rabbit models. Results: The decreased expression of CircSERPINE2 in the OA cartilage tissues was directly associated with excessive apoptosis and imbalance between anabolic and catabolic factors of extracellular matrix (ECM). Mechanistically, CircSERPINE2 acted as a sponge of miR-1271-5 p and functioned in human chondrocytes (HCs) through targeting miR-1271-5 p and ERG. Intra-articular injection of adeno-associated virus-CircSERPINE2-wt alleviated OA in the rabbit model. Conclusions: Our results reveal an important role for a novel circRNA-CircSERPINE2 in OA progression. CircSERPINE2 overexpression could alleviate HCs apoptosis and promote anabolism of ECM through miR-1271-ERG pathway. It provides a potentially effective therapeutic strategy for OA progression.